Thermal effects on particle deposition in microchannels - Yan, Zhibin (2016)
Transport and interactions of colloidal particles and biomolecules in microchannels are of great importance to many microfluidic applications, such as drug delivery in life science, microscale heat exchangers in electronic cooling, food processing industry etc. The phenomenon that particles suspended in liquid are captured by a solid surface (e.g. microchannel wall) is referred to as particle deposition. Particle deposition plays a crucial role in numerous practical applications, and is also of fundamental interest to the field of colloid science. This thesis presents studies of the thermal effects on particle deposition in microchannels, which has been a frequently “ignored” but is an important factor for thermal driven particle deposition processes at elevated temperatures. In the present study, both experimental investigation and theoretical modelling are carried out to characterise the thermal effects, including the effects of bulk solution temperature and temperature gradient in a microfluidic system. To the best knowledge of the author, this is the first attempt to investigate the thermal effect on particle deposition in microchannels. The effects of bulk solution temperature on particle deposition are investigated in a thermostatic microfluidic chip, consisting of one deposition microchannel and two minichannels used for heating from both sides of the deposition channel. This microfluidic chip provides a well-controlled bulk temperature with a good uniformity for the particle suspension (diameter: 930 nm), and allows a direct visualisation of the dynamic process of particle deposition at elevated temperatures with aid of a microscope. Experimental measurements were conducted to obtain the number of deposited particles onto the microchannel surface at various bulk solution temperatures. The experimental results show that the particle deposition rate, which is characterised by the Sherwood number, is increased by 265% with increase of the bulk solution temperature from room temperature (297.25 K) to 339.25 K. A theoretical model was derived based on the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. This model simplifies the three-dimensional particle transport phenomenon in a microchannel to a one-dimensional mass transport problem, taking into account of temperature dependence of physicochemical parameters involved in the particle deposition process. The numerically solved particle deposition rates from the one-dimensional mass transfer model agree reasonably with the experimental measurements. The model provides the interaction potential curves to describe the interactions between a microparticle and the microchannel at different temperatures. These curves show that the enhanced particle deposition observed in experiments is caused by the increased attractive interactions (van der Waals force and gravity) and the reduced repulsive interactions (electric double layer force) when increasing the bulk solution temperature. Therefore, it leads to reduced energy barriers for particle deposition at elevated temperatures. Besides, the effect of electrolyte concentration was further investigated for the particle deposition processes at elevated temperatures. The effects of temperature gradient on particle deposition were studied in a microfluidic device. The device consists of a PDMS microchannel for easy observation, an Indium tin oxide (ITO) coated glass for heating and a thermoelectric (TEC) unit for cooling to form a stable and adjustable temperature gradient across the channel. This design enables the dynamic particle deposition processes to be directly observed along the direction of the applied temperature gradient, thereby providing an effective microfluidic platform for investigating the particle-surface interaction phenomena under non-equilibrium thermal environment. Both experimental and numerical studies were carried out to examine the particle deposition under different temperature gradients. The experimental results show that the particle deposition rate (Sherwood number) is reduced by 56% when the temperature gradient inside the microchannel was increased by three orders from 78.9 K/m to 6846.9 K/m. The numerical results of particle deposition rate agree reasonably with the experimental measurements. The interaction potential curves from the numerical model suggest that the particles could experience larger resistance arising from the increased thermophoretic force in the presence of the temperature gradient, at large particle-wall distance fewer particles are transported from the bulk solution to the near-wall region. In addition, the particles need to overcome a higher energy barrier caused by the reduced bulk solution temperature in the vicinity of the channel surface, leading to the reduced particle deposition rate under a temperature gradient. Besides, for a given thermal condition, the particle deposition was observed to be further enhanced when the electrolyte concentration of the particle suspension is increased. The effects of hydrodynamic flow on the particle deposition at elevated temperatures were investigated by applying a steady flow and a pulsatile flow in the microchannel. For the steady flow, the Sherwood number is reduced with increasing the Reynolds number of the hydrodynamic flow. The reduction of particle deposition rate with Reynolds number is attributed to the increased hydrodynamic lift force which hinders the transport of particles from the bulk solution to the near-wall region. For the pulsatile flow which is generated by a specially designed pulsation generation unit, an oscillatory flow component is superimposed onto the steady flow of the particle suspension. Experiments were conducted to investigate the effect of the pulsatile flow on the particle deposition rate at different flow oscillation frequencies. The results show that the particle deposition rate can be reduced by 50% with increasing the flow oscillation frequency from 0 Hz to 1 Hz at elevated temperatures with the steady flow component being fixed at 1 mL/h.